Encyclopaedia Britannica CD 97. knowledge for the information age. - Encyclopaedia Britannica, inc. (Chicago, IL : Encyclopaedia Britannica, Inc., 1997)
Electronic encyclopedia containing the entire text of the 32-volume encyclopedia, with 72,00 articles, 8,500+ photos and illustrations, 15,000 related Internet links, 1.4 million hyperlinks, and the Merriam-Webster's collegiate dictionary, 10th ed.
Advanced search disc -- Multimedia disc.
Title from disc surface.
Issued in container (27 cm.).
Text and updates available on the Internet.
Windows system requirements: Windows 95 or Windows NT 4.0; 486 DX2/66 MHz or higher processor (Pentium recommended); 16 MB RAM (32 MB recommended); 45 MB hard disk space; 2x CD-ROM drive (4x recommended); SVGA monitor/display card 800x600, 256-colors minimum (16-bit Hicolor recommended); Windows compatible sound device (recommended); mouse; Windows-compatible printer (recommended); Internet access option reqruies 9600 baud or faster modem.
Keywords: Electronic encyclopaedia; CD-ROMs.